The Effect of Enterprise Risk Management, Intellectual Capital, and Dividend Policy on Firm Value Moderated by Good Corporate Governance - Tampubolon, Sylvana Noviakusuma; Herlina Lusmeida (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2024)
This study aims to test and empirically prove the effect of Enteprise Risk Management, Intellectual Capital, and Dividend Policy on Firm Value with Good Corporate Governance as a moderator. The source of this study uses data secondary data from companies available at S&P Capital IQ with a total of 141 observations that have met the criteria used using purposive sampling techniques . This study employed quantitative research by using multiple regression analysis with a moderator effect (Moderated ) Regression Analysis ) with the STATA program . The results of the study showed that Enterprise Risk Management had negative influence on firm value, Company policy, namely dividend policy , had positive effect on firm value, and Intellectual Capital also Good Corporate Governance had no effect on firm value. The study too showed that Good Corporate Governance as a moderator variable strengths the relationship between company policies, namely dividend policy , on firm value but Good Corporate Governance can't moderate the relationship between both Enterprise Risk Management and Intellectual Capital on firm value.